2012
DOI: 10.1002/lary.23249
|View full text |Cite
|
Sign up to set email alerts
|

Risk of superficial squamous cell carcinoma developing in the head and neck region in patients with esophageal squamous cell carcinoma

Abstract: Patients with ESCC, particularly drinkers, current smokers, and those with the ALDH2-2 allele and multiple LVLs, have an increased risk of superficial HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 18 publications
(30 reference statements)
1
57
0
2
Order By: Relevance
“…Figure 3 shows no evidence of small-study bias as confirmed with the Egger test (P ¼ 0.44) and the Begg test (P ¼ 0.53). In the sensitivity analysis, excluding the study cumulating a very high reference category compared with other studies and the absence of criteria to define second primary cancers (20), similar results were observed. Overall, similar results were also obtained in subgroup meta-analyses conducted according to study design, geographic location (Europe or Asia), or second primary cancer site; with studies assessing alcohol consumption by interview or medical record; in studies comparing drinkers versus nondrinkers or different alcohol consumption levels; studies providing data adjusted on age, gender, smoking, occupation, or index tumor site, or not.…”
Section: Uadt Second Primary Cancerssupporting
confidence: 79%
See 3 more Smart Citations
“…Figure 3 shows no evidence of small-study bias as confirmed with the Egger test (P ¼ 0.44) and the Begg test (P ¼ 0.53). In the sensitivity analysis, excluding the study cumulating a very high reference category compared with other studies and the absence of criteria to define second primary cancers (20), similar results were observed. Overall, similar results were also obtained in subgroup meta-analyses conducted according to study design, geographic location (Europe or Asia), or second primary cancer site; with studies assessing alcohol consumption by interview or medical record; in studies comparing drinkers versus nondrinkers or different alcohol consumption levels; studies providing data adjusted on age, gender, smoking, occupation, or index tumor site, or not.…”
Section: Uadt Second Primary Cancerssupporting
confidence: 79%
“…The highest category of alcohol intake in the studies ranged from drinker status to more than or equal to 170 grams per day. In most studies (11)(12)(13)(14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), alcohol consumption was assessed after primary cancer diagnosis: before treatment in 3 studies (14-16), after treatment in 5 studies (11,22,(25)(26)(27), without information about treatment in 9 studies (12, 13, 19-21, 23, 24, 28, 29). Two studies did not specify when alcohol intake was assessed (17,18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…LVLs, tumor location, and endoscopic morphology were recorded on endoscopic reports before endoscopic treatment in all cases. Multiple LVLs were defi ned as numerous, well-defi ned, irregularly shaped lesions that appeared throughout the entire esophageal mucosa aft er the application of Lugol dye solution ( 31 ). Concerning the determination of LVLs, for each patient, we recorded in a database more than 10 endoscopic photographs of the esophagus aft er instillation of iodine solution, which we reviewed to judge the grade of LVLs. "…”
Section: Methodsmentioning
confidence: 99%